New Method for the in vivo Estimation of Fluvastatin and its Application for Pharmacokinetic Studies in Rabbit - Sandhala, Deepthi; Lankalapalli, Srinivas (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The study was aimed to conduct a pharmacokinetic evaluation of Fluvastatin in rabbit plasma using a sensitive HPLC method. Materials and Methods: The plasma samples were assayed by Waters alliance e-2695 HPLC instrument using symmetry C18 column (150x4.6mm, 3.5 μ) under isocratic condition. Here the buffer was 0.1% ortho phosphoric acid. Mobile phase used was acetonitrile and 0.1% ortho phosphoric acid in 50:50 v/v with a flow rate of 1 ml/min. The eluent was monitored at 224 nm for measurement of Fluvastatin. Results: The calibration curve was linear over the concentration range of 5-200 ng/ml of Fuvastatin. Conclusion: The application denotes all the parameters of system suitability, specificity, linearity and accuracy are in good agreement with USFDA guidelines and applied effectively for the investigation of pharmacokinetic studies in rabbit.
Keywords: RP-HPLC; Fluvastatin; Rabbit Plasma; Linearity; Accuracy; Pharmacokinetics